Until ghosting do them apart: The production of subjectivity in discourses about virtual love - Silva, Francisco Vieira da (2016)
Considering the most varied discourses, currently constructed about romantic relationships that emerge by means of electronic devices, particularly flirting applications, the present text aims, from the analysis of some discursive materialities that circulated in digital media, to investigate the production of subjectivity in discourses about virtual love. For this purpose, we analyzed three media discursive materialities (two reports and a section of a magazine column). Methodologically, the present study follows a descriptive-interpretative bias, with a qualitative approach. The analysis, based on the theoretical perspective of Michel Foucault, demonstrated that, given the specificities of each studied materiality, there is the constant subjectivity production of the digital technologies user with regard specifically to the mutations in the construction of virtual love as a discourse object.Keywords: discourse, subjectivity, virtual love.